Constitutional Identity and Relations Between EU Law and Romanian Law - Toader, Tudorel; Safta, Marieta (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
This study addresses the issue of constitutional identity with reference to theoretical and practical developments in Romania, especially from the perspective of jurisprudence and the dialogue, sometimes with more tense moments, between the Romanian Constitutional Court and the Court of Justice of the European Union. In order to paint the most complete, ‘photographic’ image of the issues involved, this study presents the constitutional basis of the incorporation of EU acts into national law, the concrete method used for the incorporation, and the evolution of the jurisprudence of the Constitutional Court of Romania both in defence of national law and EU law; also presented are the development of the concept of the rule of law and the concept of constitutional identity in the Romanian doctrine and jurisprudence, highlighting the opinions expressed and the existing trends. Since the central theme of the research is dialogue as a form of shaping the concept of constitutional identity, the study ends with the fundamental milestones of this dialogue in various forms by way of preliminary references (vertically, between national courts, including constitutional ones and the CJEU); within international structures, namely associations of constitutional courts, the Venice Commission and the collaborating networks established at the level of the ECHR and the CJEU; within the various forms of bilateral cooperation. It is concluded that these forms of constitutional dialogue are well developed in Romania. However, the issue of authority relations remains latent, as shown by the recent turbulence emphasized in the study. The main conclusion is that judicial dialogue, in all its forms, represents, for now, the most appropriate solution for a balanced institutional approach to constitutional identity. Keywords: constitutional identity, rule of law, constitutional justice, judicial dialogue, Constitutional Court of Romania